2016
DOI: 10.1002/ajpa.23004
|View full text |Cite
|
Sign up to set email alerts
|

Within arm's reach: Measuring forearm length to assess growth patterns in captive bonobos and chimpanzees

Abstract: In most primates, sexual dimorphism in body size is male-biased and the differences in forearm length in chimpanzees follow this trend. Given that males of the two species did not differ in forearm length, the absence/presence of sexual dimorphism of this trait must be due to differences in somatic growth in females. Our novel method offers an alternative to obtain morphometric measures and facilitates longitudinal studies on somatic growth. Am J Phys Anthropol 161:37-43, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
(64 reference statements)
2
15
2
Order By: Relevance
“…Indeed, in our sample the forelimb (upper and lower arm) is significantly longer in chimpanzees than in bonobos (but also see Behringer et al. ), but hindlimb length (thigh and shank) is equal. Previous studies found IMI differences between both Pan species, but, while Zihlman & Cramer () stated that the tendency of the femur of P. paniscus (absolute value) to be longer influences the difference in IMI, Shea () found that this difference results from the significantly longer forelimbs of the chimpanzee.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Indeed, in our sample the forelimb (upper and lower arm) is significantly longer in chimpanzees than in bonobos (but also see Behringer et al. ), but hindlimb length (thigh and shank) is equal. Previous studies found IMI differences between both Pan species, but, while Zihlman & Cramer () stated that the tendency of the femur of P. paniscus (absolute value) to be longer influences the difference in IMI, Shea () found that this difference results from the significantly longer forelimbs of the chimpanzee.…”
Section: Discussionsupporting
confidence: 57%
“…The bonobo also has shorter forelimbs (upper and lower arms) than the chimpanzee (but also see Behringer et al. ), as well as a shorter head and a shorter foot. But when the data are scaled to body mass (i.e.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations